A Study of Efficient Factors on Consumers Purchase Motivation of Foreign Brand in Contrast with Local Brand among Consumers of Chain Stores in Kerman City - Abdolali Keshtegar (Journal of Global Pharma Technology, 2018)
The purpose of this research is investigated on effective factors on motivation of consumer purchase of foreign brand than domestic brand in Iran market. Today, consumers in developing countries like Iran and China rising by choosing between global and local brands are facing. In the competitive environment of global brands and local retailers that consumers need to know why and how these markets your brand to choose. The assumptions in this research are based on previous experience buying and preferences of the respondents, related to foreign and local Brand were evaluated. Data from a sample of customer’s convenience store chain was collected in Kerman who was selected by simple random sampling. A total of 420 customers participated in the study. This study used a questionnaire that its reliability is Cronbach's alpha equal to 0.845. The results of this study showed that using structural equation modeling. As well as consumer attitudes to global brand on perceived quality and emotional value of foreign brands have a positive effect, while the effect on Iran is different brand. Emotional value for the foreign brand is an important factor affecting purchase intention was to evaluate the effect on the Iranian brand was also approved. Concepts and applications of the study of both Iranian and foreign brands are presented in the following article.Keywords: Brand, Motivation of purchase, Brand trust, Emotional value, Perceived quality.